InSAR-based investigation of ground subsidence due to excavation: a case study of Incheon City, South Korea - Kyungwon Park; Yong Je Kim; Jiannan Chen; Boo Hyun Nam (International Journal of Geo-Engineering)
Abstract Ground subsidence is one of geohazards, particularly in urban environment due to its negative impact to nearby buildings and civil infrastructures. This study investigates the amount and spatial distribution of ground subsidence in Incheon City, South Korea, where ground excavation was made. Interferometric Synthetic Aperture Radar (InSAR) was used to monitor surface deformation around the excavation site. The study analyzed subsidence during an excavation project using Sentinel-1b satellite data, and the InSAR results were compared with traditional leveling methods and field measurements. Notable subsidence during the early construction phase was identified, which demonstrates the effectiveness of InSAR in urban environment. The research contributes to understanding of the excavation-inducing ground subsidence due to the reclamation layer.